Media Product of Let's Memorize Anima Film to Improve the Ability to Memorize Daily Prayers - Elsa Kaniawati; Nasywa Atha Kanya; Ismy Bulqis Saputri; Imam Tabroni; Zhang Wei; Murphy Xavier (Yayasan Adra Karima Hubbi, 2023)
Background. This study aims to determine the use of animated film media products let's memorize to improve the ability to memorize daily prayers. Because this research is motivated by the lack of interesting learning media in memorizing daily prayers Purpose. This study uses a research approach of Research and Development (R&D). Method. In this study the population was class 2A students of SDN 2 CITALANG, and the sample taken consisted of 15 students. Results. , Thus, judging from the results of student research. Conclusion. it is effective by using animated films let's memorize in improving the memorization ability of class 2A students of SDN 2 CITALANG.